Zespół małoocza – własne doświadczenia w leczeniu 60 pacjentów - Kobus, Kazimierz; Wójcicki, Piotr; Wysocki, Mariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The orbitoblepharophimosis syndrome is an autosomal-dominant congenital malformation involving the orbitopalpebral region. The condition is associated with orbital phimosis, upper eyelid ptosis, epicanthus and telecanthus. Material and methods: We retrospectively reviewed the records of 60 patients with blepharophimosis who underwent surgery in the Hospital of Plastic Surgery in Polanica Zdrój from January 1975 to January 2006. The study population consisted of 23 (38.3%) females and 37 (61.7%) males patients whose age at the time of first surgical stage ranged from 1 to 48 years (mean 8 years). Surgical management consisted of epicanthus correction using modified technique of Mustardé, followed by eyelid suspension to the frontalis muscle with using temporal fascia. In patients with orbitoblepharophimosis type II, correction of the lower lid ectropion and antimongoid slanting palpebral fissures, were performed before or after Mustardé procedure. Results: In our series of 60 patients, good result of treatment was obtained in 80.1% and satisfactory in 18.3% of patients. Poor outcome was obtained only in one patient with orbitoblepharophimosis type II. Conclusions: Orbitoblepharophimosis management should consists of gradual and complex surgical treatment. During the first stage epicanthus correction is performed. As a second stage, blepharoptosis is treated by frontalis suspension technique with using temporal fascia.